1972
DOI: 10.1063/1.1676984
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Relaxation Mechanism in Some Alkanethiols. II

Abstract: Dielectric constant and dielectric loss (ε′ and ε″) of four liquid alkanethiols have been measured at four microwave frequencies at 0, 20, 40, and 60°C. The normalized plots of ε′/(ε0−ε∞) vs (ε′−ε∞)/(ε0−ε∞) for all four liquids are skewed arcs. The characteristic relaxation time (τ0) and empirical parameter (β) have been calculated from these plots. The dielectric behavior of alkanethiols is more like alkyl halides than alcohols. The main mechanism which is responsible for asymmetric distribution of relaxation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1972
1972
1978
1978

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Physical properties of alkanethiols (RSH) are of interest as they are similar in structure to alcohols (ROM), which have been extensively studied in order to investigate the effect of hydrogen bonding. Krishna]i et al (6)(7)(8) have studied dielectric relaxation behavior of alkanethiols and found that the hydrogen bonding Is almost absent or too small to be detected by dielectric measurements in these compounds. The present study was undertaken to measure low frequency dielectric constants, viscosities, densities, and refractive indices of ten alkanethiols, namely, propane-1-thiol, butane-1-thiol, butane-2-thiol, 2-methylpropane-2-thiol, pentane-1-thiol, 2-methylbutane-2-thiol, hexane-1thiol, heptane-1-thiol, octane-1-thiol, and 2-methyloctane-2thiol in the temperature range 0-60 °C.…”
mentioning
confidence: 99%
“…Physical properties of alkanethiols (RSH) are of interest as they are similar in structure to alcohols (ROM), which have been extensively studied in order to investigate the effect of hydrogen bonding. Krishna]i et al (6)(7)(8) have studied dielectric relaxation behavior of alkanethiols and found that the hydrogen bonding Is almost absent or too small to be detected by dielectric measurements in these compounds. The present study was undertaken to measure low frequency dielectric constants, viscosities, densities, and refractive indices of ten alkanethiols, namely, propane-1-thiol, butane-1-thiol, butane-2-thiol, 2-methylpropane-2-thiol, pentane-1-thiol, 2-methylbutane-2-thiol, hexane-1thiol, heptane-1-thiol, octane-1-thiol, and 2-methyloctane-2thiol in the temperature range 0-60 °C.…”
mentioning
confidence: 99%